The Influence of Emotional Intelligence, Organizational Culture and Team Work On Employee Performance at The Royale Krakatau Hotel, Cilegon - Ranthy Pancasasti; Aries Pratama Putra; Fitri Nuraisah; Sofwah Khalqiyah (Program Studi S3 Ilmu Manajemen, 2022)
The purpose of this study is to analyze a model that is expected to improve employee performance by involving emotional intelligence, organizational culture and teamwork. Originality/value: Novelty in this research is that no previous research has been found that discusses emotional intelligence, organizational culture and teamwork on Employee Performance at The Royale Krakatau Hotel, Cilegon. Research limitations: The limitations of this study are only to analyze the influence of emotional intelligence, organizational culture and teamwork on employee performance at The Royale Krakatau Hotel, Cilegon. Design / methodology / approach: The research method is quantitatively by using a questionnaire with an Ordinal scale of 10 points and the sampling technique was carried out by simple random sampling. The number of samples used was 120 employees to test the four (4) predetermined hypotheses. The Structural Equation Model-Partial Least Square (SEM-PLS) model was used to test the statistical significance of the path coefficient. Findings: The findings of the study explain that Emotional Intelligence has a not significant positive effect on Employee Performance, Organizational Culture has an insignificant positive effect on Employee Performance, Emotional intelligence has a positive and significant effect on Organizational Culture, Emotional Intelligence has a positive and significant effect on Teamwork, Organizational Culture has a positive and significant effect on Teamwork, Teamwork has a positive and insignificant effect on Employee Performance.